A novel web-based system for tropical cyclone analysis and prediction - Leung, Yee-Hong; Wong, M.; Wong, K.; Zhang, W.; Leung, K. (Taylor and Francis, 2012)
A web-based system is developed for the analysis and prediction of tropical cyclones, particularly their landfalls and recurvatures. To facilitate accessibility to the system, its development is based on Google Maps application programming interface (API), Java and client/server architecture. In addition to the construction of a powerful query system for the multi-source, multi-scale and multi-level tropical cyclone database, data mining approach and dynamic modelling approach have been implemented and integrated for effective and efficient analysis, prediction and visualization of tropical cyclone movements. The system can be accessed worldwide by researchers, professionals and the general public. It is thus a powerful system for research, real-life application and knowledge dissemination. Its extensibility and user-friendliness pave the road for further development and enable more in-depth analysis and real-time operation. © 2012 Copyright Taylor and Francis Group, LLC.